2019
DOI: 10.1007/s00248-019-01358-y
|View full text |Cite
|
Sign up to set email alerts
|

How Hosts Taxonomy, Trophy, and Endosymbionts Shape Microbiome Diversity in Beetles

Abstract: Bacterial communities play a crucial role in the biology, ecology, and evolution of multicellular organisms. In this research, the microbiome of 24 selected beetle species representing five families (Carabidae, Staphylinidae, Curculionidae, Chrysomelidae, Scarabaeidae) and three trophic guilds (carnivorous, herbivorous, detrivorous) was examined using 16S rDNA sequencing on the Illumina platform. The aim of the study was to compare diversity within and among species on various levels of organization, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 65 publications
(81 reference statements)
7
46
2
Order By: Relevance
“…All strain variants characterized in these dung-beetle species are very similar to each other, but their phylogenetic tree is not congruent with that of their host. Such incongruence has been reported in many host-symbiont associations (Jäckel et al, 2013;Sontowski et al, 2015;Kolasa et al, 2019), including Wolbachiainfected insects of Madagascar (Linares et al, 2009;Zouache et al, 2011). Although it is possible that some of our Nanos dung-beetle species inherited their Wolbachia infections from a common ancestor, while others have lost or gained new infections during species radiation, our data also does not suggest radiation of Wolbachia in parallel to the radiation of N. clypeatus group.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…All strain variants characterized in these dung-beetle species are very similar to each other, but their phylogenetic tree is not congruent with that of their host. Such incongruence has been reported in many host-symbiont associations (Jäckel et al, 2013;Sontowski et al, 2015;Kolasa et al, 2019), including Wolbachiainfected insects of Madagascar (Linares et al, 2009;Zouache et al, 2011). Although it is possible that some of our Nanos dung-beetle species inherited their Wolbachia infections from a common ancestor, while others have lost or gained new infections during species radiation, our data also does not suggest radiation of Wolbachia in parallel to the radiation of N. clypeatus group.…”
Section: Discussioncontrasting
confidence: 51%
“…There, these two species, which are generalists in their choice of dung, may enter in contact and share dung patches or parasites. These ecological links may have facilitated the horizontal transfer of Wolbachia between the two species (Kolasa et al, 2019). Unfortunately, little is known about the parasitoid community associated to the Malagasy dung beetles, and no study has ever investigated the potential for dung as a suitable environment for symbiont transfer between carrion insects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, beneficial symbionts facilitate the digestion and production of limited nutrients (Dillon and Dillon, 2004;Douglas, 2009) and protect to the insect-host from pathogens (Engel and Moran, 2013). The composition of the insect gut microbiota has received great attention, it has been demonstrated that the developmental stage (Chen et al, 2016), diet type (Colman et al, 2012;Franzini et al, 2016), host taxonomy (Colman et al, 2012;Kolasa et al, 2019), environment (Ng et al, 2018), and social interactions (Martinson et al, 2012) are important factors affecting the composition and diversity of the microbial communities in the insect gut.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the bacterial diversity of arthropods may be influenced by host species (Koch et al, 2013;McFrederick et al, 2014;Martinson et al, 2017;Näpflin & Schmid-Hempel, 2018;Kolasa et al, 2019). In this study, the microbiota communities among spider mite species are variable.…”
Section: Discussionmentioning
confidence: 78%